A Systematic Literature Review of Performance Pyramids System Implementation in the Manufacture Industries - Hibarkah Kurnia (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
The prevailing literature and empirical studies on organizational performance management stress the increasing importance of non-financial performance measures and propose companies implement an integrated performance measurement system. The purpose of our research is to investigate the characteristics of performance measurement and management in various industries. This paper discusses the published literature related to the Performance Pyramids System (PPS), focusing on the latest progress in the 18 years, starting from 2002 until 2020. This paper involves the study review of 50 articles related to PPS implementation of available database search, including Google Scholar, Elsevier, Science Direct, and other publishers in the world. This literature review contains results from a variety of different perspectives. The perspective includes the industry's focus, the focus of the number of distribution by country, the year of publication, and the number of publishers. This is useful for all types of manufacturing industries to find solutions to problems. The paper also provides advantages for researchers next to add to the literature. The aims of this study are: (i) to identify the most discussed approaches in the literature to evaluate the organizational performance, and (ii) to carry out a diagnosis of how small and medium enterprises with economic activity in several countries measure and operationalize the evaluation of their performance. To meet the study's objectives, we analyzed published studies in scientific journals and conducted twelve interviews in SMEs. The results indicate that, in addition to the majority of the studied organizations not having a formal process of their strategy, they also do not measure their products in an integrated system that would allow them to evaluate according to their strategic goals.